Comparison of Music Therapy with Aromatherapy on Reducing Anxiety Levels in Preoperative Patients with Spinal Anesthesia - Wulandari, Mutiara; Sulistyanto, Benny Arief (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Patients who will undergo surgery have a high risk of anxiety, therefore the need for intervention in reducing anxiety before surgery. Objective: This study aims to compare Music Therapy with Aromatherapy on Reducing Anxiety Levels in Preoperative Patients With Spinal Anesthesia. Sample: The sampling technique used Accidental Sampling technique which was conducted for 2 weeks with a total sample of 40 respondents consisting of 20 respondents with Music Therapy and 20 respondents with Aromatherapy. Methods: This research method uses Quasy Experiment with pre test and post test group design methods. Response level of anxiety using APAIS. Results: The results showed that the difference between music therapy and aromatherapy on reducing anxiety levels in preoperative patients with spinal anesthesia obtained p value of 0.012 (< 0.05). Conclusion: In this study, it was concluded that the effect of music therapy with aromatherapy was significant to reduce anxiety levels in preoperative patients Suggestion: Hospitals are expected to improve the quality of health services, especially in the applica-tion of music with aromatherapy so as to reduce the level of anxiety in preoperative patients with spi-nal anesthesia in general hospitals.